Sistem Manajemen Risiko Melalui Aplikasi Simako Pada PT Perkebunan Nusantara VI - Sarkim, Sarkim; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2022)
Proper and optimal risk management will increase the Company's certainty in achieving its targets, and provide confidence that the Company can realize existing business opportunities by minimizing potential risks and losses that may occur. The development of Risk Management in Indonesia is currently experiencing rapid progress, because all are aware that the world is full of uncertainty that results in risks that can harm interested parties, to achieve success in the business world, uncertainty and its risks cannot be ignored, but can be minimized by Risk management. At this time PT Perkebunan Nusantara VI in the risk identification process has used a Website-based System called SIMAKO, but the risk profile report cannot be grouped based on the level of risk, so the number of risks with very high, high, medium and low categories cannot be known and this It is very difficult for the user to identify all the risks that have been previously inputted, the system that has been implemented by researchers has changed the output results as desired by the company management.